Development of the prosencephalic structures, ganglionic eminence, basal ganglia and thalamus at 11 + 3 to 13 + 6 gestational weeks on 3D transvaginal ultrasound including normative data - R. Altmann; T. Rechberger; C. Altmann; L. Hirtler; I. Scharnreitner; P. Stelzl; S. Enengl (Brain Structure and Function, 2023)
Objectives To show the development of ganglionic eminence, basal ganglia and thalamus/hypothalamus in week 11 + 3 to 13 + 6 by transvaginal 3D ultrasound. Methods To visualize the prosencephalic structures surrounding the 3rd ventricle, 285 three-dimensional ultrasound volume blocks from 402 fetuses examined were selected in a prospective transvaginal 3D study to compare ultrasound images of ganglionic eminence, basal ganglia, thalamus/hypothalamus with embryological sections. In addition, measurements of the described structures were made in 104 fetuses to quantify the embryological development. Results The sonomorphologic characteristics of ganglionic eminence, basal ganglia and thalamus/hypothalamus are described in 71% of the fetuses examined. Measurements of the structures in 57% of the fetuses, show the following results: axGE ap = 0.17 + 0.112*CRL; axGE/I = 0.888 + 0.048*CRL; axGE/BG = 0.569 + 0.041*CRL; coGE/BG = 0.381 + 0.048*CRL; coTh lat = − 0.002 + 0.135*CRL; coTh/HyT = 3.68 + 0.059*CRL; co3.V lat = 0.54 + 0.008*CRL. Conclusion Transvaginal 3D neurosonography allows visualization and measurement of normal structures in the fetal prosencephalon at 11 + 3 to 13 + 6 weeks of gestation (GW) including details of ganglionic eminence (GE), basal ganglia (BG), and thalamus/hypothalamus (Th/HyT). Further scientific work is needed before using the results to decide on pathological changes in patients.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Multi-omics-based prediction of hybrid performance in canola - Dominic Knoch; Christian R. Werner; Rhonda C. Meyer; David Riewe; Amine Abbadi; Sophie Lücke; Rod J. Snowdon; Thomas Altmann (Theoretical and Applied Genetics, 2021)
Key message Complementing or replacing genetic markers with transcriptomic data and use of reproducing kernel Hilbert space regression based on Gaussian kernels increases hybrid prediction accuracies for complex agronomic traits in canola . In plant breeding, hybrids gained particular importance due to heterosis, the superior performance of offspring compared to their inbred parents. Since the development of new top performing hybrids requires labour-intensive and costly breeding programmes, including testing of large numbers of experimental hybrids, the prediction of hybrid performance is of utmost interest to plant breeders. In this study, we tested the effectiveness of hybrid prediction models in spring-type oilseed rape ( Brassica napus L./canola) employing different omics profiles, individually and in combination. To this end, a population of 950 F 1 hybrids was evaluated for seed yield and six other agronomically relevant traits in commercial field trials at several locations throughout Europe. A subset of these hybrids was also evaluated in a climatized glasshouse regarding early biomass production. For each of the 477 parental rapeseed lines, 13,201 single nucleotide polymorphisms (SNPs), 154 primary metabolites, and 19,479 transcripts were determined and used as predictive variables. Both, SNP markers and transcripts, effectively predict hybrid performance using (genomic) best linear unbiased prediction models (gBLUP). Compared to models using pure genetic markers, models incorporating transcriptome data resulted in significantly higher prediction accuracies for five out of seven agronomic traits, indicating that transcripts carry important information beyond genomic data. Notably, reproducing kernel Hilbert space regression based on Gaussian kernels significantly exceeded the predictive abilities of gBLUP models for six of the seven agronomic traits, demonstrating its potential for implementation in future canola breeding programmes.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Genetic diversity for nitrogen use efficiency in Arabidopsis thaliana - Rhonda C. Meyer; Corina Gryczka; Cathleen Neitsch; Margarete Müller; Andrea Bräutigam; Armin Schlereth; Hardy Schön; Kathleen Weigelt-Fischer; Thomas Altmann (Planta, 2019)

Climate and Land Cover Analysis Suggest No Strong Ecological Barriers to Gene Flow in a Natural Baboon Hybrid Zone - Tim L. Wango; Douglas Musiega; Charles N. Mundia; Jeanne Altmann; Susan C. Alberts; Jenny Tung (International Journal of Primatology, 2019)

Does climate variability influence the demography of wild primates? Evidence from long‐term life‐history data in seven species - Fernando A. Campos; William F. Morris; Susan C. Alberts; Jeanne Altmann; Diane K. Brockman; Marina Cords; Anne Pusey; Tara S. Stoinski; Karen B. Strier; Linda M. Fedigan (Global Change Biology, 2017)
Earth's rapidly changing climate creates a growing need to understand how demographic processes in natural populations are affected by climate variability, particularly among organisms threatened by extinction. Long‐term, large‐scale, and cross‐taxon studies of vital rate variation in relation to climate variability can be particularly valuable because they can reveal environmental drivers that affect multiple species over extensive regions. Few such data exist for animals with slow life histories, particularly in the tropics, where climate variation over large‐scale space is asynchronous. As our closest relatives, nonhuman primates are especially valuable as a resource to understand the roles of climate variability and climate change in human evolutionary history. Here, we provide the first comprehensive investigation of vital rate variation in relation to climate variability among wild primates. We ask whether primates are sensitive to global changes that are universal (e.g., higher temperature, large‐scale climate oscillations) or whether they are more sensitive to global change effects that are local (e.g., more rain in some places), which would complicate predictions of how primates in general will respond to climate change. To address these questions, we use a database of long‐term life‐history data for natural populations of seven primate species that have been studied for 29–52 years to investigate associations between vital rate variation, local climate variability, and global climate oscillations. Associations between vital rates and climate variability varied among species and depended on the time windows considered, highlighting the importance of temporal scale in detection of such effects. We found strong climate signals in the fertility rates of three species. However, survival, which has a greater impact on population growth, was little affected by climate variability. Thus, we found evidence for demographic buffering of life histories, but also evidence of mechanisms by which climate change could affect the fates of wild primates.

Resource base influences genome‐wide DNA methylation levels in wild baboons ( Papio cynocephalus ) - Amanda J. Lea; Jeanne Altmann; Susan C. Alberts; Jenny Tung (Molecular Ecology, 2016)
Variation in resource availability commonly exerts strong effects on fitness‐related traits in wild animals. However, we know little about the molecular mechanisms that mediate these effects, or about their persistence over time. To address these questions, we profiled genome‐wide whole‐blood DNA methylation levels in two sets of wild baboons: (i) ‘wild‐feeding’ baboons that foraged naturally in a savanna environment and (ii) ‘Lodge’ baboons that had ready access to spatially concentrated human food scraps, resulting in high feeding efficiency and low daily travel distances. We identified 1014 sites (0.20% of sites tested) that were differentially methylated between wild‐feeding and Lodge baboons, providing the first evidence that resource availability shapes the epigenome in a wild mammal. Differentially methylated sites tended to occur in contiguous stretches (i.e., in differentially methylated regions or DMR s), in promoters and enhancers, and near metabolism‐related genes, supporting their functional importance in gene regulation. In agreement, reporter assay experiments confirmed that methylation at the largest identified DMR , located in the promoter of a key glycolysis‐related gene, was sufficient to causally drive changes in gene expression. Intriguingly, all dispersing males carried a consistent epigenetic signature of their membership in a wild‐feeding group, regardless of whether males dispersed into or out of this group as adults. Together, our findings support a role for DNA methylation in mediating ecological effects on phenotypic traits in the wild and emphasize the dynamic environmental sensitivity of DNA methylation levels across the life course.

Dent and Flint maize diversity panels reveal important genetic potential for increasing biomass production - R. Rincent; S. Nicolas; S. Bouchet; T. Altmann; D. Brunel; P. Revilla; R. A. Malvar; J. Moreno-Gonzalez; L. Campo; A. E. Melchinger; W. Schipprack; E. Bauer; et al. (Theoretical and Applied Genetics, 2014)

Sources of variance in a female fertility signal: exaggerated estrous swellings in a natural population of baboons - Courtney L. Fitzpatrick; Jeanne Altmann; Susan C. Alberts (Behavioral Ecology and Sociobiology, 2014)

Costs of reproduction in a long-lived female primate: injury risk and wound healing - Elizabeth A. Archie; Jeanne Altmann; Susan C. Alberts (Behavioral Ecology and Sociobiology, 2014)

When good neighbors don't need fences: temporal landscape partitioning among baboon social groups - A. Catherine Markham; Vishwesha Guttal; Susan C. Alberts; Jeanne Altmann (Behavioral Ecology and Sociobiology, 2013)

Effect of gestational protein deficiency and excess on hepatic expression of genes related to cell cycle and proliferation in offspring from late gestation to finishing phase in pig - Simone Altmann; Eduard Murani; Cornelia C. Metges; Manfred Schwerin; Klaus Wimmers; Siriluck Ponsuksili (Molecular Biology Reports, 2012)

Prediction of hybrid biomass in Arabidopsis thaliana by selected parental SNP and metabolic markers - Matthias Steinfath; Tanja Gärtner; Jan Lisec; Rhonda C. Meyer; Thomas Altmann; Lothar Willmitzer; Joachim Selbig (Theoretical and Applied Genetics, 2010)

“Friendships” between new mothers and adult males: adaptive benefits and determinants in wild baboons (Papio cynocephalus) - Nga Nguyen; Russell C. Van Horn; Susan C. Alberts; Jeanne Altmann (Behavioral Ecology and Sociobiology, 2009)

Genetic evidence reveals temporal change in hybridization patterns in a wild baboon population - J. TUNG; M. J. E. CHARPENTIER; D. A. GARFIELD; J. ALTMANN; S. C. ALBERTS (Molecular Ecology, 2008)
The process and consequences of hybridization are of interest to evolutionary biologists because of the importance of hybridization in understanding reproductive isolation, speciation, and the influence of introgression on population genetic structure. Recent studies of hybridization have been enhanced by the advent of sensitive, genetic marker‐based techniques for inferring the degree of admixture occurring within individuals. Here we present a genetic marker‐based analysis of hybridization in a large‐bodied, long‐lived mammal over multiple generations. We analysed patterns of hybridization between yellow baboons ( Papio cynocephalus ) and anubis baboons ( Papio anubis ) in a well‐studied natural population in Amboseli National Park, Kenya, using genetic samples from 450 individuals born over the last 36 years. We assigned genetic hybrid scores based on genotypes at 14 microsatellite loci using the clustering algorithm implemented in structure 2.0, and assessed the robustness of these scores by comparison to pedigree information and through simulation. The genetic hybrid scores showed generally good agreement with previous morphological assessments of hybridity, but suggest that genetic methods may be more sensitive for identification of low levels of hybridity. The results of our analysis indicate that the proportion of hybrids in the Amboseli population has grown over time, but that the average proportion of anubis ancestry within hybrids is gradually decreasing. We argue that these patterns are probably a result of both selective and nonselective processes, including differences in the timing of life‐history events for hybrid males relative to yellow baboon males, and stochasticity in long‐distance dispersal from the source anubis population into Amboseli.

Age at maturity in wild baboons: genetic, environmental and demographic influences - M. J. E. CHARPENTIER; J. TUNG; J. ALTMANN; S. C. ALBERTS (Molecular Ecology, 2008)
The timing of early life‐history events, such as sexual maturation and first reproduction, can greatly influence variation in individual fitness. In this study, we analysed possible sources of variation underlying different measures of age at social and physical maturation in wild baboons in the Amboseli basin, Kenya. The Amboseli baboons are a natural population primarily comprised of yellow baboons ( Papio cynocephalus ) that occasionally hybridize with anubis baboons ( Papio anubis ) from outside the basin. We found that males and females differed in the extent to which various factors influenced their maturation. Surprisingly, we found that male maturation was most strongly related to the proportion of anubis ancestry revealed by their microsatellite genotypes: hybrid males matured earlier than yellow males. In contrast, although hybrid females reached menarche slightly earlier than yellow females, maternal rank and the presence of maternal relatives had the largest effects on female maturation, followed by more modest effects of group size and rainfall. Our results indicate that a complex combination of demographic, genetic, environmental, and maternal effects contribute to variation in the timing of these life‐history milestones.

Divided destinies: group choice by female savannah baboons during social group fission - Russell C. Van Horn; Jason C. Buchan; Jeanne Altmann; Susan C. Alberts (Behavioral Ecology and Sociobiology, 2007)

Social relationships among adult female baboons (Papio cynocephalus) II. Variation in the quality and stability of social bonds - Joan B. Silk; Susan C. Alberts; Jeanne Altmann (Behavioral Ecology and Sociobiology, 2006)

Social relationships among adult female baboons (papio cynocephalus) I. Variation in the strength of social bonds - Joan B. Silk; Jeanne Altmann; Susan C. Alberts (Behavioral Ecology and Sociobiology, 2006)

Segregation distortion in Arabidopsis C24/Col-0 and Col-0/C24 recombinant inbred line populations is due to reduced fertility caused by epistatic interaction of two loci - Ottó Törjék; Hanna Witucka-Wall; Rhonda C. Meyer; Maria von Korff; Barbara Kusterer; Carsten Rautengarten; Thomas Altmann (Theoretical and Applied Genetics, 2006)

Growth rates in a wild primate population: ecological influences and maternal effects - Jeanne Altmann; Susan C. Alberts (Behavioral Ecology and Sociobiology, 2005)

The Arabidopsis PHD-finger protein SHL is required for proper development and fertility - C. Müssig; A. Kauschmann; S. D. Clouse; T. Altmann (Molecular Genetics and Genomics, 2000)

Fate and effects of micropollutants in the Gironde estuary, France: a multidisciplinary approach - C. Amiard-Triquet; S. Altmann; J. C. Amiard; C. Ballan-Dufrançais; P. Baumard; H. Budzinski; C. Crouzet; P. Garrigues; E. His; A. Y. Jeantet; R. Menasria; P. Mora; et al. (Hydrobiologia, 1998)

Cadmium mobilisation under conditions simulating anaerobic to aerobic transition in a landfill leachate-polluted aquifer - R. Scott Altmann; Alain C. M. Bourg (Water, Air, & Soil Pollution, 1997)

CADMIUM MOBILISATION UNDER CONDITIONS SIMULATING ANAEROBIC TO AEROBIC TRANSITION IN A LANDFILL LEACHATE-POLLUTED AQUIFER - R. SCOTT ALTMANN; ALAIN C. M. BOURG (Water, Air, & Soil Pollution, 1997)

Human papillomavirus type 16 (HPV 16) E7 and major histocompatibility complex (MHC) class I and II expression in human keratinocytes in culture - A. Hoos; C. D'Incan; L. Gissmann; A. Altmann; F. Momburg; I. Nindl; W. Osen; BH. Schönning; I. Jochmus (Archives of Virology, 1996)

Preparation and activation: determinants of age at reproductive maturity in male baboons - Susan C. Alberts; Jeanne Altmann (Behavioral Ecology and Sociobiology, 1995)